KONTRIBUSI KEBIASAAN MEMBACA DAN MOTIVASI BELAJAR TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP PEMBANGUNAN LABORATORIUM UNP - Jasni, Martika; Atmazaki, Atmazaki (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The purpose of this study is three. First, to describe the contribution of reading habits to the writing text exposition skills of class VIII students of SMP Pembangunan Laboratorium UNP. Second, to describe the contribution of learning motivation to the writing exposition text students of class VIII of SMP Pembangunan Laboratorium UNP. Third, describe the contribution of reading habits and learning motivation to the writing skills of exposition students of VIII grade SMP Pembangunan Laboratorium UNP. This type of research is quantitative research using descriptive methods and correlational designs. The population in this study were students of class VIII of the SMP Pembangunan Laboratorium UNP 2018/2019 academic year totaling 167 people. The sample in this study was determined by proportional random sampling, 25% of the population, namely 43 students. The data of this study were scores on the results of the reading habits questionnaire, scores on the results of the questionnaire of learning motivation, and the results of the test of writing the text of the esposition. The instruments used in this study were reading habits questionnaire, learning motivation questionnaire, and performance tests to measure exposition text writing skills. There are three research results in this study. First, reading habit significantly contributes to the writing skills of exposition text students of class VIII of SMP Pembangunan Laboratorium UNP by 15.21%. Secondly, motivation to learn significantly contributed to the writing skills of exposition students of VIII grade at SMP Pembangunan Laboratorium UNP by 30.25%. Third, reading habits and learning motivation together contribute to the writing skills of exposition text students of class VIII of SMP Pembangunan Laboratorium UNP by 35.35%. Kata kunci: Kontribusi, Kebiasaan Membaca, Motivasi Belajar, Keterampilan Menulis Teks Eksposisi